BIOFILM FORMATION AND ANTIBIOTIC SUSCEPTIBILITY OF UROPATHOGENS IN PATIENTS WITH CATHETER ASSOCIATED URINARY TRACT INFECTIONS IN IBB CITY -YEMEN - Saleh, Amr Abdu Mohammed; Al-Shamahy, Hassan A.; Al-Hrazi, Roqiaa Mohammed Ahmed; Jaadan, Bushra Mohammed; AL-Magrami, Rahma Taher Farea; Al-Sharani, Amani Abdulhakeem (Universal Journal of Pharmaceutical Research, 2020)
Objective: Biofilm formation by uropathogens on the surface of indwelling medical devices can inflict obstinate or recurring infection, thought-provoking antimicrobial therapy. This study included 227 patients with indwelling urinary catheters and suffering from CAUTI. They were analyzed for biofilm formation and antibiogram susceptibility, 59.4% were males and 40.6% were females. Methods: Ensuing phenotypic identification of isolated bacteria, antibiotic sensitivity test was performed by modified Kirby–Bauer disc diffusion method following the Clinical and Laboratory Standards Institute (CLSI 2015) guidelines; Biofilm-forming uropathogens were detected by the tissue culture plate (TCA) method. Results: The predominant uropathogen in catheter-associated UTIs (CAUTIs) was Escherichia coli 46.3%, followed by K. pneumoniae18.5%, P. aeruginosa 11.9%,7%, S. coagulase negative 5.7%, S. aureus 4.8%, Enterobacter spp. 4.4%, E. faecalis 1.3%. The total rate of biofilm producer bacteria was 49.3% (21.1% high producers, 28.2% moderate producers). Prime biofilm producers were E. coli 60% with OR=8.6 (p=0.002), followed by K. pneumoniae 57.1% with OR=10.1 (p=0.002), and P. aeruginosa 37% with OR=6.6 (p=0.02). Gram-negative biofilm producers found 100%, 100%, 88.6%, 82.9%, 81.9%, 80.9%, and 72.4%, 40%, 33% resistant to ampicillin , amoxyclave, cotrimoxazole, ceftraxone, nalidixic acid, ciprofloxacin, cefotaxime, nitrofurantoin and amikacin respectively. Conclusion: In conclusion, a high antimicrobial resistance was observed in biofilm producers than non-biofilm producers. Of recommended antimicrobial therapies for CAUTIs, ampicillin and amoxicillin-clavulanate were the least active antibiotics, whereas imipenem and amikacin were found as the most effectual for gram-negative biofilm producer. Likewise, penicillin and erythromycin were the least active antibiotics, whereas vancomycin, and rifampicin were found as the most effective antibiotic for Gram-positive biofilm producer. Peer Review History: Received 8 October 2019; Revised 6 November; Accepted 27 December; Available online 15 January 2020 Academic Editor: Rola Jadallah , Arab American University, Palestine, rola@aauj.edu Reviewer(s) detail: Dr. Mujde Eryilmaz , Ankara University,Turkey, meryilmaz@ankara.edu.tr Dr. Tamer Elhabibi , Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com